Perancangan Sistem Aplikasi Pemesanan Soto Ayam Pringgading Berbasis Website Dengan Metode Waterfall - Angga Dwi Jayanto (Jurnal Penelitian Ilmu komputer, 2023)
Responding to increasingly competitive competition in every business, gave rise to the idea of integrating information technology with business. Virtual ordering describes a wide range of information technology, processes and practices in online business transactions without using manual transaction tools. By using online ordering, companies can market a product or service to consumers with a worldwide reach, so that from a business perspective it is a good opportunity to expand the market share of the products or services offered. This thesis research aims to analyze and create an Application System for Ordering Soto Ayam Pringgading Website Based Using the Waterfall Method which can provide the information needed by consumers. With this system, Soto Ayam Pringgading Ciputat can build an internet-based product ordering system that can eliminate distance limitations. and time. The development tools used by researchers are PHP as the application interface and My SQL as the database. These were all chosen because of their reliability in making web-based applications. On this occasion, the author only discusses the ordering service system through cash payments (either in person or via bank transfer). And the development of a web-based ordering service system is only applied to the marketing and sales of Soto Ayam Pringgading Ciputat.